Effectiveness of Natrum Muriaticum 1M on Reduction of TSH Level in Females between Age Group 35 to 55 Years (Advancements in Homeopathic Research, 2022)
Hypothyroidism is a current issue in Southern parts of India, which has been identified today as a prevalent disease among adult population of India. [1]. For many decades even modern physicians were trying hard to find scope in thyroid dysfunctions. A prospective randomized clinical study was conducted as Single group, experimental, pre and post study devoid of control. The study was carried out at the OPDs of Sarada Krishna Homoeopathic Medical College &Hospital. Cases were followed up to six months and assessment was done once in 3 months.This study concludes that Natrum Muriaticum 1M was effective in the management of hypothyroidism.
Keywords: devoid; cases; clinical; opd